Activated hippo signal pathway inhibits cell proliferation and promotes apoptosis in NK/T cell lymphoma cells. (23rd May 2019) - Chang, Yu; Fu, Xiao‐Rui; Cui, Meng; Li, Wei‐Ming; Zhang, Lei; Li, Xin; Li, Ling; Sun, Zhen‐Chang; Zhang, Xu‐Dong; Li, Zhao‐Ming; You, Xiao‐Yan; Nan, Fei‐Fei; et al.
Abstract: Background: Natural Killer T–Cell Lymphoma (NKTCL) is a subtype of Non‐Hodgkin's Lymphoma, and its morbidity is ranked the first of T‐Cell Lymphoma. Hippo signaling pathway is involved in the pathogenesis of tumors. However, the role of Hippo signaling pathway in the oncogenesis of NKTCL still remains unclear. Methods: The expressions of mammalian sterile 20‐like kinase 1 (MST1) and Yes‐associated protein (YAP) were investigated by RT‐PCR and Western blotting. Cell viability was detected by MTT assays. Cell cycle and cell apoptosis were determined by flow cytometry. Cell proliferative capacity was detected by colony formation assay. Nude mice xenograft models were established and the tumor sections were analyzed by immunohistochemistry (IHC) staining. Results: The expression of MST1 was significantly down‐regulated in NKTCL tissues (n = 30) and cell lines, while the expression of YAP was significantly up‐regulated, and the phosphorylation of YAP was inhibited. Overexpression of MST1, knockdown of YAP, or verteporfin (VP) treatment could inhibit cell proliferation, and promote cell cycle arrest and apoptosis in NKTCL cells, while knockdown of MST1 and overexpression of YAP promoted cell proliferation. Additionally, Bcl‐2/Bax ratio and downstream effectors of Hippo signaling pathway (c‐myc, survivin, cyclinD1, CTGF, and TEAD) were significantly decreased when MST1 was overexpressed and YAP was knocked down or after VP treatment. Furthermore, our mice model demonstrated that activation of Hippo signal pathway suppressed the tumorigenesis of NKTCL. Conclusion: The activation of Hippo signal pathway via overexpressing MST1 or down‐regulating YAP can inhibit the tumorigenesis of NKTCL. Abstract : This study is conducive for us to better understanding the pathogenesis of NKTCL, and looking for the key molecular markers during the disease progression, so as to provide help for early diagnosis.